EKSISTENSI MAYSIR DI KABUPATEN GORONTALO - Khair, Fathul; Hasri, Muammar; Suleman, Abdul Majid (IAIN BONE, 2025)
Gorontalo as the Veranda of Medina is one of the reasons for having cultural and customary values ​​that are closely related to the Qur'an and Islam. The practice of maysir that has begun to exist in the Gorontalo Regency community is contrary to the culture and customs of Gorontalo which are based on the Qur'an. This study aims to explain the form of maysir practice in Gorontalo Regency and explain the causes of maysir practice in Gorontalo Regency. This study is a qualitative study. Two forms of maysir or gambling that are often carried out by the Gorontalo Regency community are boat racing and kite games. Kite games and boat racing in Gorontalo Regency are maysir because they fulfill the four elements of maysir. The two implementations of maysir in Gorontalo Regency have several similarities and also have several of the same causes. The perpetrators of maysir in Gorontalo Regency are not equipped with good and correct religious knowledge. Furthermore, although the majority of Gorontalo society is now Muslim, rejection of Islam in Gorontalo also occurred and continues to this day, one of which is the implementation of maysir which occurred in Gorontalo Regency. Coupled with the influence of parties from outside the Gorontalo society who provide understandings that are not in accordance with Gorontalo customs.